2006
DOI: 10.1093/toxsci/kfl064
|View full text |Cite
|
Sign up to set email alerts
|

Dehydroepiandrosterone Inhibits Complex I of the Mitochondrial Respiratory Chain and is Neurotoxic In Vitro and In Vivo at High Concentrations

Abstract: Dehydroepiandrosterone (DHEA) is widely used as a food supplement and considered to be relatively safe. In animal studies, however, additions of high concentrations of DHEA to the diet have led to hepatotoxicity as well as liver mitochondrial dysfunction. This study was therefore designed to find out whether DHEA is able to inhibit the respiratory activity also in neuronal mitochondria and to reveal whether this leads to functional disturbance in the brain. Using different mitochondrial substrates, we show her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 47 publications
1
28
0
Order By: Relevance
“…DHEA is known to affect mitochondrial energy production through inhibition of enzymes associated with the respiratory chain [48] with variable findings in children with ASD [49], [50].…”
Section: Discussionmentioning
confidence: 99%
“…DHEA is known to affect mitochondrial energy production through inhibition of enzymes associated with the respiratory chain [48] with variable findings in children with ASD [49], [50].…”
Section: Discussionmentioning
confidence: 99%
“…There are several animal studies that used a similar DHEA dose (6 g/kg of diet or 0.6%) to investigate the effects of feeding DHEA on several metabolic changes including weight loss using the Zucker rat model [8,21]. However, there is one study that used regular mice and not obese Zucker rats, and the study reported that mice fed with pellets containing 0.6% DHEA for 3 months showed a significant neuronal loss in the cerebral cortex and hippocampus, a slightly decreased dopamine/dihydroxyphenylacetic acid ratio, and motor impairment [28]. However, there are no reports of toxicity when using 6 g/kg of diet in the obese Zucker rat model.…”
Section: Methodsmentioning
confidence: 99%
“…The administration of 500 nM DHEA (the highest concentration examined) was neurotoxic to rat hippocampal cultures [150]. High concentrations of DHEA (micromolar concentrations) have also been neurotoxic in vitro , with effects mediated through inhibition of complex I of the mitochondrial respiratory chain [269]. Neurotoxic effects have also been demonstrated in vivo .…”
Section: Neurobiological Actions Of Dhea(s)mentioning
confidence: 99%